Mitochondrial (dys) function: a double edge sword in cell stress response - Guaragnella, Nicoletta; Di Noia, Maria Antonietta; Primavera, Angela (Frontiers in Cell Death, 2024)
Mitochondria are multifaceted organelles acting as energy, metabolic and signaling hubs in the cells. They play a central role in biological processes aimed at maintaining cell homeostasis and regulating cell fate upon changing environments. Alterations in mitochondrial functions can affect cell stress response through different mechanisms, leading to adaptation or death. In this perspective, we focus on mitochondrial communication and its relevance for cytoprotective strategies aimed at controlling synthesis, degradation and recycling processes. The advantage of using yeast as a model organism for improving our understanding of the molecular mechanisms behind cell stress responses to mitochondrial dysfunction is described. New challenges for studying the interplay between mitochondrial retrograde signaling and autophagy/mitophagy pathways are highlighted.